STUDENTS’ PERCEPTIONS OF EFFECTIVE LECTURER TEACHING - Mohamad Kamil Ariff Khalid; Normala Ismail (Journal of Islamic, Social, Economics and Development, 2020)
Lecturers play an important role in education, teaching and learning processes. The process of teaching and learning involves the interaction between students and lecturers. The purpose of this study is to examine the students’ perspective on the effectiveness of lecturers’ teaching. The sample consists of 300 Diploma students from various faculties who study at Universiti Teknologi MARA (UiTM) Pahang, Raub Campus. The instrument was a questionnaire distributed to the respondents using stratified random sampling. The data was analysed using the Statistical Package for Social Sciences (SPSS) version 23. This study found that the effectiveness of lecturers’ teaching can be seen from the aspect of personality, teaching behaviour, relationship and attitude of lecturers towards students. The findings also show that there are five main characteristics in the lecturers’ personality which are of students’ choice; friendly, firm, caring, punctual and diligent. The Multiple Regression Analysis results show that the lecturers’ knowledge and teaching experience are the dominant factors that influence the students’ grades. Furthermore, this study did not deny that the lecturers’ personality who are friendly, easily approachable and loves to joke are also significant estimators for their academic achievement. The researcher hopes through this study lecturers can diversify their efforts so that the teaching and learning process can be smooth and fun to attract students to strive for their best.